Love and Marriage in the Twelfth Century - Welckenhuysen, Andries (eds) (Mediaevalia Lovaniensia - Series 1/Studia, 1984)
Love, the mightiest feeling that can inspirit human beings, and Marriage, the institution which, if not animated by this feeling, loses its sense and its soul, form the topics of this book, just as they were the themes of the Colloquium which, from May 16th to 18th 1978, was organized by the 'lnstituut voor Middeleeuwse Studies' at the 'KU Leuven'. In fact, the fifteen papers collected here originate from communications held at this Colloquium. They focus in essence on 12th century society, culture and thought in Western Europe. However, it is unavoidable, and self-evident too, that more than one contribution bursts through this rather narrow compass, either to broach the currents in which certain phenomena are to be seen, or to open perspectives on surrounding cultures or contiguous periods.